Assessment of the Penetration of an Endodontic Sealer into Dentinal Tubules with Three Different Compaction Techniques Using Confocal Laser Scanning Microscopy - Ignacio Barbero-Navarro; Diego Velázquez-González; María Esther Irigoyen-Camacho; Marco Antonio Zepeda-Zepeda; Paulo Mauricio; David Ribas-Perez; Antonio Castano-Seiquer (Journal of Functional Biomaterials, 2023)
Adequate root canal sealing is essential for the success of endodontic treatment. There are numerous techniques available; identifying simple and efficient techniques is important to provide good patient care. The purpose of the study was to compare the maximum penetration depth and the percentage of sealant penetration of an endodontic sealer into dentine tubules using cold lateral condensation, continuous wave, and hybrid techniques, and to contrast the effectiveness of two different tapered gutta-percha master cones (0.02 and 0.04). A sample of sixty single root teeth was used. Six experimental groups were formed from the three filling techniques and the two tapered master cones. Images were acquired using a confocal laser scanning microscope. In the apical root third, the penetration percentage was higher in the hybrid compared with the continuous wave technique. The results indicated a higher penetration depth of hybrid compared with cold lateral condensation in the middle and coronal thirds, and in the apical third, a higher penetration was identified in the hybrid group compared with the continuous wave group. No significant differences in penetration were found comparing 0.02 with 0.04 taper gutta-percha groups. The coronal cross-sections presented a higher penetration than the apical third sections. In conclusion, the hybrid technique a had higher maximum sealer penetration than the continuous wave in the apical third, and the coronal third hybrid and continuous wave had a higher penetration than cold lateral condensation.